The Influence of Quantum Learning Model Assisted by Nearpod on Students’ Self Confidence Levels in Learning of Genetics in XII MIPA MAN Lumajang - RISMA, KHARISMA; Heni Setyawati (Universitas Islam Negeri Walisongo Semarang, 2025)
The results of the pre-study showed that the self confidence of students in class XII MIPA MAN Lumajang was relatively low, as students tend to be shy about asking questions and expressing their opinions due to monotonous learning models and media. Through the Quantum Learning model, students’ persistence and courage will grow in interpreting difficult biology material such as genetics. Student active participation will also be supported by Nearpod features. The purpose of this study was to determine the significant effect of Quantum Learning model assisted by nearpod on self-confidence. The research approach was quantitative with a quasi experimental design. The research design uses a nonequivalent pretest-posttest control group design with Mann Whitney U-Test data analysis technique. The results showed that the experimental class's self-confidence obtained a mean questionnaire score of 90.27, which was higher than the control class's score of 74.69. The Mann Whitney U-Test results from the posttest obtained a Sig. value of 0.000 < 0.05, meaning that there was a significant effect of the Nearpod-assisted Quantum Learning model on students' self-confidence.